The direct and indirect effects of self‐efficacy on salespeople's emotional exhaustion and work‐family conflict: A study using the job demands‐resources model - Carballo-Penela, Adolfo; Varela-Aldás, José; Bande Videla, Belén (Canadian Journal of Administrative Science-Revue Canadienne des Science de l'Administration, 2019)
This study integrates Social Cognitive Theory with the Job Demands-Resources Model to examine self-efficacy in relation to emotional exhaustion and work-family conflict (WFC) in a sample of 192 employees. The results obtained through structural equation analysis show: a negative association between self-efficacy and both work overload and emotional exhaustion; a positive relationship between work overload and both emotional exhaustion and WFC; that work overload mediates the relation between self-efficacy and both emotional exhaustion and WFC; that role ambiguity moderates the relation of self-efficacy with work overload; and that tenure in the sales territory moderates the relation of work overload with WFC.
Keywords: self-efficacy; emotional exhaustion; work overload; work-family conflict; job demands-resources model; JCR; Scopus